Guanaco’s diet and forage preferences in Nothofagus forest environments of Tierra del Fuego, Argentina - Quinteros, Claudia-Pamela; Bava, José-Omar; Gobbi, Miriam-Edith; Defossé, Guillermo-Emilio (Forest Systems, 2017)
Aim of study: Guanaco (Lama guanicoe Müller), is a South American native ungulate widely distributed in Patagonia, which in the island of Tierra del Fuego (TF), extends its habitat into Nothofagus spp. forests. Within these forests, guanacos consume lenga (Nothofagus pumilio) leaves and twigs, and other understory species. The aim of this work was to determine: 1) the spring and summer diet of free ranging guanacos, and 2) which plants, grown in the forest understory, guanacos do prefer, or avoid, in these seasons of great forage abundance.Area of study: Tierra del Fuego (Argentina), on three representative areas which combined Nothofagus forests and adjacent meadows (vegas).Material and Methods: Guanacos’ diet was determined by comparing epidermal and non-epidermal plant fragments with micro-histological analyses of feces. The analysis was made from composite samples of fresh feces, collected at the seasons of maximum forage productivity (spring and summer).Main results: During spring, 48% of guanacos’ diet was composed of lenga leaves, 30% of grass-like species, 15% of grasses, and less than 7% of herbs, shrubs, and lichens. In summer, 40% of the diet was composed of grasses, 30% of lenga leaves, 25% of grass-like species and the rest corresponded to herbs, shrubs, and lichens. Within the forest understory, guanaco selected lenga leaves and twigs, grass species were consumed according to their availability (or sometimes rejected), while other herbs were not consumed at all.Research highlights: Guanacos’ consumption preference for lenga, even considering the high availability of other forages, could adversely affect forest regeneration.